A highly efficient In2S3/Ag2S/TiO2 NTAs photoelectrodes for photocathodic protection of Q235 carbon steel under visible light. (22nd January 2023) - Li, Hong; Yang, Zhanyuan; Cui, Xingqiang; Li, Yanhui; Zhang, Pengfei; Li, Junru
Abstract: A novel In2 S3 /Ag2 S/TiO2 nanotube arrays (NTAs) was successfully fabricated by successive ionic layer adsorption and reaction method and electrochemical anodic oxidation method, and served as photoanode for photocathodic protection application. The micromorphologies, optical absorption properties, crystalline structure and elemental valence states of the composites were performed by field emission scanning electron microscopy, high resolution transmission electron microscope, UV–vis diffuse reflectance absorption spectra, x-ray diffractometer and x-ray photoelectron spectroscopy, respectively. The photocathodic protection performances of In2 S3 /Ag2 S/TiO2 NTAs on the Q235 carbon steel (CS) were also studied. The In2 S3 /Ag2 S/TiO2 nanocomposites show better photoelectrocatalytic and photocathodic protection performance than pure TiO2 NTAs. The photocurrent density of In2 S3 (9)/Ag2 S(8)/TiO2 photoelectrode coupled with Q235 CS reach 211 μ A cm −2, which is about 4.5 times higher than that of TiO2 NTAs. The photogenerated potential of Q235 CS coupled to In2 S3 (9)/Ag2 S(8)/TiO2 under illumination shows a negative shift to −0.92 V versus SCE. Results indicate that the co-sensitization of In2 S3 and Ag2 S could extend the light absorption of TiO2 to the visible light range and enhance its photoelectric conversion efficiency.